Vídeos interativos na formação de professores de matemática - Campos, Arthur Ferreira (2024)
This research highlighted the potential results obtained from the use of interactive videos in the first period of a subject in the in-person Mathematics course at a public university. As these classes were applied in times of a pandemic, the modality was developed remotely through the Microsoft Teams virtual environment, which made remote classes possible. As methodological procedures, we observed the participants in the learning platform, together with the teacher of the Elementary Mathematics Seminars subject, with the objective of preparing university students for a modern and dynamic approach, through facilitating tools for making interactive videos. In this educational environment, we witnessed the adaptation of different languages of media such as television and internet apps, such adaptation was intended to create a language closer to the usual. The participation of undergraduates, resulted in the production of videos where it was possible analyze the challenges faced, receive their feedback, evaluate them, among other records. All data produced was systematized, which made it possible to highlight the importance of the Technological Pedagogical Content Knowledge. In view of all this investigation, the deduction was reached that interactive videos with mathematical content are now part of the life of undergraduates. As a result of this research, a digital product was developed as an ebook titled: Interactive Video: Exotic Wheels for Mathematics Teacher Formation.